Plasma concentration of atorvastatin metabolites correlates with low‐density lipoprotein cholesterol reduction in patients with coronary heart disease - E. Sverre; J. Munkhaugen; O. Kristiansen; H. Weedon‐Fekjær; K. Peersen; E. Gjertsen; L. Gullestad; S. Bergan; E. Husebye; N. T. Vethe (Wiley, 2023)
Abstract In this exploratory study from a randomized double‐blinded crossover trial including 70 patients with coronary heart disease and self‐perceived muscular side effects of statins, we aimed to determine the relationship between low‐density lipoprotein cholesterol (LDL‐C) reduction and atorvastatin metabolite plasma concentrations. All patients underwent a 7 weeks treatment period with atorvastatin 40 mg/day and a 7 weeks placebo period in random order. Nonlinear regression with a three‐parameter equation explored the relationship between percentage LDL‐C reduction (statin vs. placebo) and the pharmacokinetic variables. Mean LDL‐C reduction was 49% (range 12% to 71%). The sum of 4‐OH‐atorvastatin acid and lactone correlated moderately with the LDL‐C response (Spearman ρ 0.27, 95% confidence interval [CI]: 0.03 to 0.48). Accordingly, nonlinear regression showed R2 of 0.14 (95% CI: 0.03 to 0.37, R2 adjusted equaled 0.11). Even a perfect underlying correlation of 1.0 showed R2 = 0.32 by simulation, using historical intra‐individual LDL‐C variation (8.5%). The 90% inhibitory concentration was 2.1 nmol/L, and the 4‐OH‐metabolite sum exceeded this threshold in 34% of the patients. In conclusion, trough plasma concentrations of 4‐OH‐atorvastatin metabolites correlated moderately to the LDL‐C reduction. A plateau LDL‐C response was observed above a pharmacokinetic threshold, below which the response was highly variable. The usefulness of monitoring concentrations of atorvastatin metabolites to optimize the individual dosage have limitations, but its supportive potential may be pursued in relevant patient subsets to achieve adequate efficacy at the lowest possible dose. The results add knowledge to the overall understanding of the variable LDL‐C response mediated by atorvastatin.